C.1 - Abramovitz Moses ...[et al] (California, 1961)
This collection of essays has to do primarily with allocation and dis tribution of economic resources. As colleagues and students of Professor Haley, the authors of these papers have greatly benefited from his learning and spirit of critical inquiry in this large and important field of economic research. It is with a deep sense of gratitude, admiration, and affection that the contributors dedicate the present volume to Bernard Francis Haley on the occasion of his sixtieth birthday.
Keywords: Economics